Interest rates and the market for new light vehicles - Adam Copeland; George J. Hall; Louis J. Maccini (Federal Reserve Bank of New York, 2015)
We study the impact of interest rate changes on both the demand and supply of new light vehicles in an environment where consumers and manufacturers face their own interest rates. An increase in the consumers' interest rate raises their cost of financing and thus lowers the demand for new vehicles. An increase in the manufacturers' interest rate raises their cost of holding inventories. Both channels have equilibrium effects that are amplified and propagated over time through inventories, which serve as a way to both smooth production and facilitate greater sales at a given price. Through the estimation of a dynamic stochastic market equilibrium model, we find evidence of both channels at work and of the important role played by inventories. A temporary 100 basis point increase in both interest rates causes vehicle production to fall 12 percent and sales to fall 3.25 percent at an annual rate in the short run.
Keywords: E44; G31; 330; interest rates; automobiles; inventories; Bayesian maximum likelihood